Baclofen into the lateral parabrachial nucleus induces hypertonic sodium chloride and sucrose intake in rats - De Oliveira, L. B. [UNESP]; Kimura, E. H. [UNESP]; Callera, J. C. [UNESP]; De Luca, L. A. [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; Menani, José Vanderlei [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
GABA(A) and GABA(B) receptors are present in the lateral parabrachial nucleus (LPBN), a pontine area involved with inhibitory mechanisms related to the control of sodium appetite. Activation of GABA(A) receptors in the LPBN induces strong ingestion of 0.3 M sodium chloride (NaCl) in normonatremic and euhydrated rats. In the present study, we investigated the effects of the GABA(B) receptor agonist baclofen, injected alone or combined with GABA(A) or GABA(B) receptor antagonists into the LPBN on 0.3 M NaCl, water, 0.06 M sucrose and food intake in normonatremic and euhydrated rats. Male Holtzman rats with stainless steel cannulas implanted bilaterally in the LPBN were used. In normonatremic and euhydrated rats, bilateral injections of baclofen (0.5 nmol/0.2 mu l) into the LPBN induced 0.3 M NaCl (24.0 +/- 3.1 vs. saline: 2.0 +/- 0.8 ml/240 min) and water intake (10.6 +/- 1.4 vs. saline: 3.5 +/- 0.7 ml/240 min) in a two-bottle test. Injections of GABA(B) receptor antagonists CGP 35348 (50 nmol/0.2 mu l) or 2-hydroxysaclofen (5 nmol/0.2 mu l) or GABA(A) receptor antagonist bicuculline (1.6 nmo1/0.2 mu l) into the LPBN reduced 0.3 M NaCl (14.1 +/- 4.7 ml/240 min; 9.97 +/- 2.5 ml/210 min; 8.8 +/- 5.9 ml/240 min, respectively) and water intake induced by baclofen injected into the LPBN. Baclofen (0.5 nmo1/0.2 mu l) injected into the LPBN also induced 0.06 M sucrose intake (21.8 +/- 5.9 vs. saline: 5.0 +/- 2.6 ml/180 min). Urinary volume and sodium excretion had a tendency to decrease after baclofen injection into the LPBN, whereas arterial pressure and food intake were not affected. The results show that baclofen injected into the LPBN, in normonatremic and euhydrated rats, produces a natriorexigenic effect dependent on GABAA and GABA(B) receptor activation. The natriorexigenic effect is not secondary to alterations in blood pressure or sodium urinary excretion. In addition, baclofen injected into the LPBN also induces 0.06 M sucrose intake. (C) 2011 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; sucrose intake; water intake; GABA receptors; urinary excretion; blood pressure